Genotypes maize for biomass and grains of second season cultivation in Dourados-MS - Guimarães, Amanda Gonçalves (2023)
Maize is a versatile crop, which allows from the production of whole plant silage to the harvest of grain maize, but it is necessary to verify the genotypes with these potentials according to the region of cultivation. Thus, the objective of this work was to identify the aptitude of maize for biomass for silage and grain in two years of second season cultivation in Dourados-MS. The experiment was conducted at Embrapa Western Agriculture, Dourados, MS, Brazil under field conditions in the experimental design was in randomized complete block in a 6x2 factorial scheme be six maize genotypes (BRS1010, KWS9606, BRS3046, 1P2224, 1Q2383, CAPO) and two growing years (2021 and 2022) with five replications. The agronomic traits of plant biomass for silage (plant and ear heigh, stem diameter number of leaves, green mass yield plant, leaf, steam more tassel and ear, dry matter yield in the plant and efficiency of land) and maize grain (ear diameter ear length, number of grain rows per ear, number of grains per row in ears, hundred seed weight and grain yield) were evaluated. There was an increase in the values of the traits for whole maize plant in the year 2022 compared to the year 2021. The maize genotypes indicated for biomass for silage were BRS3046, KWS9606 and 1Q2383, as for maize grain, the experimental genotypes that are under development, 1P2224 and 1Q2383, are promising options for the region.